Workaholism as a Trigger for Marital Conflict: Psychological and Legal Perspectives - Nurul Firdaus; Bustanul Arifien Rusydi (Institut Agama Islam Negeri Metro, 2024)
Workaholism is a phenomenon that is increasingly prevalent in modern society. While working is a positive activity, excessive focus on work can trigger an imbalance between professional and personal life. In the context of marriage, this imbalance can lead to conflicts, relationship breakdowns, and even divorce. A concrete example of the impact of workaholism on family life can be found in the Bantul Religious Court Decision No. 840/Pdt.G/2022/PA.Btl. In this case, workaholism was cited by the plaintiff as the reason for filing for divorce in court. This study employs a library research method with descriptive-analytical analysis of the court ruling as the object of research. The purpose is to explore the psychological and legal impacts of workaholism from a psychological perspective using the work-family conflict theory and the theory of spouses of workaholics. Additionally, the maslahah mursalah approach is used to assess whether workaholism as a social phenomenon brings benefits or harms. The findings of this study reveal that workaholism can trigger disputes between married couples, leading to divorce. From the perspective of maslahah mursalah, workaholism provides benefits, such as fulfilling the family’s economic needs and achieving career goals. Moreover, there is also harm, such as being a trigger for conflicts within the household.